High Expression of Nicotinamide Adenine Dinucleotide Phosphate Oxidase 4 Correlates with High Grade of Clear Cell Renal Cell Carcinoma - Rezeki, Dewi Sri; Laksmi, Lidya Imelda; Mariedina, Causa Trisna; Alferraly, T. Ibnu; Lukito, Joko S.; Betty, Betty (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2024)
Background Clear cell renal cell carcinoma (ccRCC) is the most common histological subtype in renal cell tumors (RCT). This is a very aggressive cancer, often diagnosed at advanced stage leading to increase morbidity and mortality rates. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 4 (NOX-4) expression plays role in the regulation of several cancer types. The expression of NOX-4 is associated with a poorer degree of differentiation and a shorter survival in RCT. Therefore, NOX-4 expression is predictor of prognosis and potential therapeutic target. Research on the correlation of NOX-4 expression in RCTs is still very limited, while Correlation of NOX-4 expression in ccRCC does not exist yet. Objective To assess the relationship between NOX-4 expression and ISUP grading in ccRCC. Method In this study, 30 slide samples and ccRCC paraffin blocks were diagnosed histopathologically at Department of Anatomic Pathology of H. Adam Malik General Hospital from January 2012 to April 2022. All clinicopathological data were taken from medical records/pathology archives. The expression of NOX-4 immunohistochemical was assessed in nucleus and cytoplasm of tumor cells. The assessment was carried out semiquantitatively based on intensity and percentage of expressed tumor cells. The relationship between NOX-4 expression and ISUP grading was assessed using Fisher's exact test. Results Of the 30 ccRCC samples, high grade ccRCC was found in 21 cases (70%) and strong expression of NOX-4 in cytoplasm and nucleus in 20 cases (66.7%). Strong expression of NOX-4 in high grade ccRCC was found in 17 cases (81.0%). A significant relationship was observed between NOX-4 expression and ISUP grading on ccRCC with a p-value of 0.030 (p<0.05) using Fisher's exact test. Conclusion There is a significant relationship between NOX-4 expression and ISUP grading in ccRCC. Therefore, NOX-4 expression can be used for the prognosis of ccRCC and therapy development.